Mrs. Lizzy is dizzy! - Gutman, Dan; Paillot, Jim (New York, NY Scholastic Inc., 2016)
Ella Mentry School's newest teacher, Mrs. Lizzy, has some very strange ideas about learning during recess.
110805
Keywords: Schools -- Juvenile fiction; Teachers -- Juvenile fiction; School recess breaks; Humorous fiction; Juvenile works